PODCAST-MEDIATED LISTENING INSTRUCTION IN EFL CLASSROOMS: EVIDENCE FROM BBC LEARNING ENGLISH IN INDONESIA - Dita Aprida; Huriyah; Edy Waloyo (UIN Siber Syekh Nurjati Cirebon, 2026)
This study aimed to investigate the effect of BBC Learning English podcasts on students’ listening comprehension in English as a Foreign Language (EFL) classrooms. The research employed a quantitative approach using a quasi-experimental design involving an experimental class and a control class at one public junior high school in Cirebon during the 2025/2026 academic year. The participants were eighth-grade students categorized as intermediate EFL learners. The data were collected through pre-test and post-test listening comprehension tests to measure students’ ability in understanding spoken English. The experimental class received listening instruction using BBC Learning English podcasts, while the control class was taught using conventional textbook-based listening materials. The findings showed that the mean score of the experimental class increased from 42.58 to 66.77, whereas the control class improved from 42.78 to 54.81. Furthermore, the independent samples t-test revealed a significance value of 0.007, which was lower than 0.05, indicating a significant difference between both groups. The study concludes that BBC Learning English podcasts had a positive and significant effect on students’ listening comprehension. Therefore, BBC Learning English podcasts can be used as an effective and meaningful listening learning resource for intermediate EFL students.